2007
DOI: 10.1161/circresaha.107.155655
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Integrin–Vascular Endothelial Growth Factor Receptor Cross-Activation in Angiogenesis

Abstract: Abstract-The functional responses of endothelial cells are dependent on signaling from peptide growth factors and the cellular adhesion receptors, integrins. These include cell adhesion, migration, and proliferation, which, in turn, are essential for more complex processes such as formation of the endothelial tube network during angiogenesis. This study identifies the molecular requirements for the cross-activation between ␤ 3 integrin and tyrosine kinase receptor 2 for vascular endothelial growth factor (VEGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
284
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(301 citation statements)
references
References 28 publications
12
284
0
5
Order By: Relevance
“…Although we have not investigated UPARANT/FPR association and disassociation process, we found that an excess of UPARANT prevents fMLF binding to FPR, suggesting that fMLF and UPARANT share the same binding site. The pivotal role of avb3 in mediating VEGF-dependent proangiogenic stimulus is well established (35). The involvement of avb3 integrin in the UPARANT inhibitory effect is supported by the findings that cell adhesion to vitronectin is greatly reduced in the presence of UPARANT.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although we have not investigated UPARANT/FPR association and disassociation process, we found that an excess of UPARANT prevents fMLF binding to FPR, suggesting that fMLF and UPARANT share the same binding site. The pivotal role of avb3 in mediating VEGF-dependent proangiogenic stimulus is well established (35). The involvement of avb3 integrin in the UPARANT inhibitory effect is supported by the findings that cell adhesion to vitronectin is greatly reduced in the presence of UPARANT.…”
Section: Discussionmentioning
confidence: 85%
“…It is known that avb3 integrin has a prominent role in the activity of VEGF. In response to VEGF, b3 integrin regulates integrin-dependent actin reorganization, thus leading avb3-VEGFR2 complexes to localize at new formed focal adhesions (35). UPARANT caused disappearance of avb3 at focal adhesions and the appearance of thin, avb3-positive linings at the cell edge, similar to untreated cells, whereas the addition of 10 nmol/L ERFR did not modify VEGF-dependent integrin redistribution.…”
Section: Uparant Competes With Fmlf For Binding To the Formyl-peptidementioning
confidence: 86%
“…Thus, VEGF receptor-mediated activation of FAK via c-Src allows formation of FAK-␣v␤5 integrin signaling complexes (46). Furthermore, VEGF induces ␣3 integrin tyrosine phosphorylation via c-Src, regulating adhesion and migration of endothelial cells (47).…”
Section: Discussionmentioning
confidence: 99%
“…Among several integrins, ␣ v ␤ 3 is the most abundant and influential receptor regulating angiogenesis, and its tumor cell expression is correlated with disease progression in various tumor types (19). Growing evidence supports a central role for cooperative signaling between ␣ v ␤ 3 integrin and growth factor receptors, such as ErbB-2 (20), platelet-derived growth factor receptor ␤ (21,22), and vascular endothelial growth factor receptor 2 (21,23), mediating tumor cell adhesion, migration, invasion, and survival, as well as endothelial cell activation (19). In the same line, we have previously shown interaction of ␣ v ␤ 3 with the PTN receptor protein-tyrosine phosphatase ␤/ (RPTP␤/), which is required for PTN-induced endothelial cell migration (24).…”
Section: Nucleolin (Ncl)mentioning
confidence: 99%